Statistical analysis of precipitation, temperature and snow cover in Bhagirathi river basin (MAUSAM, 2022)
One of the world’s largest river basins is the Ganga River basin. Bhagirathi basin which is part of this Ganga Basin is important because the glacier (Gangotri) from which river Ganga originates is situated in this basin. The present study presents the changing climate impact on dynamics of snow cover and hydrological regime of the Bhagirathi basin. The remote sensing satellite data from MODIS, TRMM and Cartosat DEM are used and watershed delineation, snow cover area extraction, trend and correlation analysis are performed in ArcGIS and R statistical software respectively. The results of trend analysis show a negative and weak association in precipitation data and positive but weak association in temperature data. However, when correlation analysis was done for different stations in the basin a strong positive correlation was found among the precipitation and temperature data for Kendall (0.93), Spearman (0.99) and Pearson (0.99) methods. A weak correlation was found between inflow and percentage snow cover area in the Bhagirathi basin for Kendall (0.04), Spearman (0.06) and Pearson (0.07) methods. The study findings present an insight into the precipitation, temperature and snow cover area data statistically. Further a better understanding of the data can be established if sub-basin level study is performed.